2022
DOI: 10.29244/jpsl.12.1.97-111
|View full text |Cite
|
Sign up to set email alerts
|

Mapping mangrove forest distribution on Banten, Jakarta, and West Java Ecotone Zone from Sentinel-2-derived indices using cloud computing based Random Forest

Abstract: Mangrove ecosystem is a very potential area, generally located in ecoton areas (a combination of intertidal and supratidal areas), where there is interaction between waters (sea, brackish water, and rivers) with land areas. Indonesia, especially the Banten and West Java regions, have vast mangrove areas and are currently under threat of land conversion. Moreover, mapping the distribution of mangrove forests using the Google Earth Engine platform based on Cloud Computing is less published. Therefore, this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Therefore, the built-up land class is found in all resorts in UKNT. In the case of mangroves, this study found 1,897.88 ha, whereas, in previous studies, the area of mangroves in this national park was 547.34 ha (Asy'Ari et al, 2022). This is considered necessary for an evaluation of the LULC classification process.…”
Section: Constraints and Limitations: Index Assessment And Classifica...contrasting
confidence: 52%
“…Therefore, the built-up land class is found in all resorts in UKNT. In the case of mangroves, this study found 1,897.88 ha, whereas, in previous studies, the area of mangroves in this national park was 547.34 ha (Asy'Ari et al, 2022). This is considered necessary for an evaluation of the LULC classification process.…”
Section: Constraints and Limitations: Index Assessment And Classifica...contrasting
confidence: 52%
“…The NDVI value of mangroves in the Dong Rui commune is greater when compared to the NDVI value of the Can Gio mangrove forest region, a typical mangrove forest area in southern Vietnam (Hoa et al 2020). Dong Rui commune mangroves have NDVI and GNDVI values that are comparable to those found on Sumatra's eastern coast (NDVI = 0.738 and GNDVI = 0.641) (Samsuri et al 2021) and greater than those found in the Banten, Jakarta, and West Java Ecotone Zones (NDVI: 0.39 -0.61 and GNDVI: 0.25 -0.48) (Asy' Ari et al 2022).…”
Section: Discussionmentioning
confidence: 93%
“…One area with mangrove ecotourism potential is the beach KSS, Tangerang Regency, Banten (Kurniawansyah et al, n.d.). In 1996 it was stated that there was a mangrove forest area of 487.5 in Tangerang Regency (Asy'Ari et al, 2022). However, as time goes by, there is a decrease in the area of mangrove forests and only 182.14 ha remain (Marlianingrum et al, 2021); (TW et al, 2022).…”
Section: Introductionmentioning
confidence: 99%